2020
DOI: 10.1186/s12920-020-00730-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes and miRNA associated with idiopathic recurrent pregnancy loss: an exploratory data mining study

Abstract: Background: Recurrent pregnancy loss (RPL) is a significant adverse pregnancy complication, with an incompletely understood pathology. While many entities were proposed to elucidate the pathogenic basis of RPL, only few were significant enough to warrant investigation in all affected couples.. The aim of this study was to provide novel insights into the biological characteristics and related pathways of differentially expressed miRNA (DEMs) and genes (DEGs), in RPL, and construct a molecular miRNAs-mRNAs netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…There are many factors that affect early pregnancy abortion. Numerous investigations have indicated that chromosomal abnormalities, antiphospholipid syndrome, congenital structural abnormalities of the uterus, type I diabetes, and thyroid dysfunction may lead to spontaneous abortion in early pregnancy (2). However, other than these known risk factors, still almost half of the cause spontaneous abortion are unclear and further explanation is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…There are many factors that affect early pregnancy abortion. Numerous investigations have indicated that chromosomal abnormalities, antiphospholipid syndrome, congenital structural abnormalities of the uterus, type I diabetes, and thyroid dysfunction may lead to spontaneous abortion in early pregnancy (2). However, other than these known risk factors, still almost half of the cause spontaneous abortion are unclear and further explanation is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, 34 differentially expressed miRNAs were reported in EPL, which were found to be enriched in several regulatory pathways, including TNF and TGF‐β signaling pathways. A study reported changes in expression of miR‐378a‐3p and miR‐371a‐5p modulating apoptotic pathways associated with EPL and RPL, respectively (Bahia et al, 2020; E. Du, Cao, et al, 2019; Hong et al, 2018). Yang et al (2018) also reported deregulated expression of several miRNAs leading to irregularity in non‐invasiveness in recurrent miscarriage, leading to pregnancy loss.…”
Section: Ncrnas In Women's Healthmentioning
confidence: 99%
“…Emerging evidence also suggests that microRNAs are key regulators of maternal-fetal communication during pregnancy, and can play a fundamental roles in blastocyst implantation, embryonic development and maintenance of pregnancy [17][18][19]. Altered expression levels of miRNAs have been reported in various pathophysiological conditions, including idiopathic recurrent pregnancy loss (iRPL) [20,21]. In addition to being are expressed in different cell types and tissues, miRNAs are released in extracellular body uids such as plasma, serum, urine, tears, saliva and seminal uid [22].…”
Section: Introductionmentioning
confidence: 99%